Parent–child relationships in Latinx families: The role of immigrant concentration, residential stability, and generational status. Issue 7 (27th July 2020) - Riina, Elizabeth M.; Lippert, Adam M.
Abstract: Prior research links neighborhood immigrant concentration and residential stability to individual health outcomes. It remains unclear how neighborhood social organization extend to family functioning among immigrant families. Expanding the scope of research on neighborhoods and family relationships, this study draws on data from 1417 Latinx families ( M youth age  = 10.19 years, SD youth age  = 3.34) to: (1) examine associations between neighborhood immigrant concentration, residential stability, and parent–child warmth and conflict in Latinx families, and (2) test whether associations vary by family generational status. Multilevel mod3els revealed that associations between immigrant concentration and parent–child relationships were contingent on residential stability, and that the association differed according to generational status. In general, stable neighborhoods with larger immigrant populations were associated with more warmth and less conflict for first‐ and second‐generation families relative to foreign‐born families. Discussion centers on the conditional role of neighborhood structural characteristics for family relationships among Latinx families and advances directions for future research on neighborhoods and families.